Pemberdayaan Mahasiswa Wirausaha Melalui Digitalisasi dan Penguatan Kapasitas Bisnis Berkelanjutan - Puspita Lianti Putri; Iin Dyah Indrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to empower student entrepreneurs through digitalization and strengthening sustainable business capacity. The activities are comprehensively designed with a participatory and experiential learning approach, so that participants not only understand the concepts theoretically but also are able to apply them practically. The program consists of various activities, such as interactive workshops on digital marketing and sustainable business models, business clinics to analyze current business problems, digitalization simulations using online platforms, individual mentoring sessions by business practitioners, and presentations of business plans developed by each participant. A total of 30 students from various study programs were actively involved and demonstrated high enthusiasm throughout the process. A total of 30 students from various study programs were actively involved and demonstrated high enthusiasm throughout the process. Program evaluation was conducted through observation, questionnaires, and assessments of the developed digital action plans. The evaluation results showed significant improvements in cognitive aspects (understanding of digitalization concepts, sustainable business models, and digital marketing strategies), affective (interest and commitment to business development), and application (the ability to develop and present innovative business plans relevant to digital challenges). Ninety percent of participants were able to develop digital action plans that encompassed the use of social media, e-commerce, digital payment systems, and technology integration in business operations. Furthermore, the program encouraged collaboration among students in building business networks and young entrepreneur communities. Positive participant feedback demonstrated that the participatory approach and hands-on practice were effective in increasing student motivation and readiness to face business challenges in the digital era. The program has proven effective in enhancing students' entrepreneurial competencies and fostering an adaptive business mindset.